Congenital mesoblastic nephroma: A case report - Hatim K Al-Turkistani (Wolters Kluwer Medknow Publications, 2008)
Congenital mesoblastic nephroma (CMN) is a rare renal tumor. It can be detected antenatally especially with judicious use of ultrasonography. A premature female neonate 28 weeks' gestation, complicated by polyhydramnios, was born to a 28-year-old woman. An abdominal mass was detected antenatally. At the end of the first week of life, the newborn had hypertension that was controlled by hydralazine. Ultrasonography and CT scan showed a right-sided renal heterogeneous solid mass. Right nephrectomy was performed and the histology showed CMN.